Twelve tips for academic role and institutional change in distance learning. (2nd January 2015) - Delgaty, Laura
Abstract: Background : With the uptake of distance learning (DL), which has been marginal for most clinical academics, teaching contexts, traditional power structures and relationships have changed, leaving lecturers potentially disenfranchised. DL has caused a distinct change in academic roles, but academic and institutional routines have remained unchanged. Information surrounding the changes is confusing and lacks clear guidance. Aim : To provide a pragmatic outline of roles, responsibilities, obstacles and solutions for clinical academics involved in DL. Method : A two-year action research project was carried out examining the academic role when developing and delivering a 20 credit post graduate DL module in Clinical Education at Newcastle University. It entailed three strands which were "active" for two weeks at a time in which all activities had to be completed. Sixteen students participated in the module consisting of independent activities, facilitated discussion forums, wikis, required reading, individual and group tasks. Pedagogically, it was based on heavily on Garrison's (2012) and Salmon's (2008) work on constructivism and online communities. Results : Institutions need a clear plan and a change of culture. Roles have emerged including: administrator, manager, team leader knowledge expert, moderator and facilitator. Conclusions : Universities struggle to engage staff with DL due to its unrecognis ed and (many academics believe) unsustainable workload. These 12 tips provide academics and managers involved in clinical education with clear guidance surrounding strategies that inform practice. New roles have emerged, work habits must be revolutionised and changes in routine must be addressed.